ANALISIS PELAKSANAAN PEMBELAJARAN KURIKULUM MERDEKA DI KELAS IV SD ISLAM PESANGGRAHAN SEMARANG - Fajar Hammid; Ferina Agustini; Ikha Listyarini (STKIP Subang, 2023)
The background that drives this research is teacher planning in using the independent learning curriculum, this is due to curriculum renewal caused by the decline in knowledge and skills (learning loss) after distance learning during the Covid 19 pandemic. The purpose to be achieved in this study is to find out teacher planning in learning using the independent learning curriculum and to find out the factors that support and inhibit the implementation of the independent learning curriculum. This type of research is qualitative research in the form of analysis. The subjects in this study were grade IV teachers and grade IV teachers of SD Muhammadiyah 16 Semarang. Data in the study were obtained through interviews, observation and documentation. The results showed that teachers in planning learning activities using the independent learning curriculum require extra preparation. Teachers must prepare learning according to the needs and abilities of students while each student has different needs and abilities. Based on the results of the research, the suggestion that can be conveyed is that teachers develop learning in accordance with the concept of an independent learning curriculum. The school or school principal can conduct additional training to support and improve the competence of educators and educators. For readers, it is hoped that by reading this thesis they will be able to understand how teacher preparation in planning learning using the independent learning curriculum.